THE INFLUENCE OF BRAND IMAGE AND ADVERTISING ON CONSUMER BUYING BEHAVIOR IN TELKOMSEL 4G PACKAGE PLAN - Umboh, Frederik Jibrael; Tielung, Maria V.J. (Universitas Sam Ratulangi, 2016)
This research is about to analyze the influence of brand image and advertising on consumer buying behavior in Telkomsel 4G package plan. Consumer buying behavior plays an important role to increase sales of a company’s product. In order to attract consumer buying behavior, company need to implement some strategies to increase their sales. Strategy that must be considered by Telkomsel to increase 4G users they are building a stronger brand image and massive promotion through their advertising so the consumers will more trust, know and use Telkomsel 4G network service. This research is a quantitative research and using multiple regression analysis. The respondent of this research are the users of Telkomsel 4G. These researches conclude that there is a significant influence of brand image and advertising on consumer buying behavior simultaneously and partially. This study suggests to Telkomsel management should further improve brand image and advertising to make the consumers attract and using Telkomsel 4G product. Keywords: consumer buying behavior, brand image, advertising